2009
DOI: 10.1016/j.ijid.2008.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with increased prevalence of human papillomavirus infection in a cohort of HIV-infected Brazilian women

Abstract: The estimated prevalence of high-risk HPV-infection among HIV-infected women from Rio de Janeiro, Brazil, was high. Close monitoring of HPV-related effects is warranted in all HIV-infected women, in particular those of younger age and advanced immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
51
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 49 publications
19
51
4
3
Order By: Relevance
“…Data from previous studies found that cofactors increased the positivity of HPV among women living with HIV such as age greater than or equal to 35 years and greater partners [49,50]. However, in our study, none of the demographic factors was associated with HPV infection.…”
Section: Discussioncontrasting
confidence: 88%
“…Data from previous studies found that cofactors increased the positivity of HPV among women living with HIV such as age greater than or equal to 35 years and greater partners [49,50]. However, in our study, none of the demographic factors was associated with HPV infection.…”
Section: Discussioncontrasting
confidence: 88%
“…Esses exames foram realizados de maneira não cega, isto é, os examinadores tinham conhecimento do resultado do exame citológico ao realizarem a colposcopia, sendo ele verdadeiro para o exame histopatológico. Maiores detalhes sobre outros procedimentos e análises epidemiológicas relacionadas à coorte podem ser encontradas na literatura 25,26 .…”
Section: Métodosunclassified
“…20,21 As such, HIV-infected women in Brazil may be at heightened risk for the development and progression of HPV-induced disease. Among HIV-infected women, studies from Brazil have evidenced a high prevalence of HPV infection 22 and increased risk to progression from HSIL to invasive cervical cancer. 23 Thus, it is necessary to provide consistent cervical cancer screening and to link screening and care in such a manner that it ensures effective treatment.…”
Section: Introductionmentioning
confidence: 99%